Particle-in-cell Simulations of Global Relativistic Jets with Helical Magnetic Fields. Issue Volume 12:Issue S324(2016) (23rd June 2017) - Duţan, Ioana; Nishikawa, Ken-Ichi; Mizuno, Yosuke; Niemiec, Jacek; Kobzar, Oleh; Pohl, Martin; Gómez, Jose L.; Pe'er, Asaf; Frederiksen, Jacob T.; Nordlund, Åke; Meli, Athina; Sol, Helene; et al.
Abstract: We study the interaction of relativistic jets with their environment, using 3-dimen- sional relativistic particle-in-cell simulations for two cases of jet composition: (i) electron-proton ( e − − p + ) and (ii) electron-positron ( e ± ) plasmas containing helical magnetic fields. We have performed simulations of "global" jets containing helical magnetic fields in order to examine how helical magnetic fields affect kinetic instabilities such as the Weibel instability, the kinetic Kelvin-Helmholtz instability and the Mushroom instability. We have found that these kinetic instabilities are suppressed and new types of instabilities can grow. For the e − − p + jet, a recollimation-like instability occurs and jet electrons are strongly perturbed, whereas for the e ± jet, a recollimation-like instability occurs at early times followed by kinetic instability and the general structure is similar to a simulation without a helical magnetic field. We plan to perform further simulations using much larger systems to confirm these new findings.